組織の老化のマーカー及びその使用 (2022)
【課題】胎盤組織、皮膚、腎臓、及び脳組織を含む組織の老化及び／又は酸化損傷を検出又は判定する方法を提供する。【解決手段】本明細書では、胎盤組織、皮膚、腎臓、及び脳組織を含む組織の老化及び／又は酸化損傷を検出又は判定する方法が提供される。一実施形態は、体組織の老化を検出又は判定するための方法を提供し、この方法は、生物学的試料中のアルデヒドオキシダーゼ１（ＡＯＸ１）の発現又は活性の１つ又は複数のマーカーを測定することを含み、ＡＯＸ１の発現若しくは活性又は１つ若しくは複数のマーカーのレベルが組織の老化の指標である。本明細書では、１つ又は複数の細胞又は組織の老化又は酸化損傷に関連する疾患又は状態を処置する方法も提供され、この方法は、ＡＯＸ１の阻害剤を、それを必要とする対象に投与することを含む。【選択図】図１ Provided herein are methods of detecting or determining aging and/or oxidative damage in tissue, including placental tissue, skin, kidney and brain tissue. One embodiment provides a method for detecting or determining aging in body tissue, comprising measuring one or more markers of aldehyde oxidase 1 (AOX1) expression or activity in a biological sample, wherein the level of AOX1 expression or activity, or of the one or more markers, is indicative of aging in the tissue. Also provided herein are methods of treating a disease or condition associated with ageing or oxidative damage in one or more cells or tissues, comprising administering to a subject in need thereof an inhibitor of AOX1.